Analytical and preparative chromatographic procedures for obtaining pure cresyl violet and cresyl red from commercial cresyl violet. (April 2015) - Urrutia, MN; Ortiz, CS
Abstract: Cresyl violet and cresyl red, components of commercial cresyl violet acetate, were separated and purified using preparative column liquid chromatography. The stationary phase was silica gel and gradient elution was carried out using chloroform:methanol. The purified dyes were obtained in high yield; 51% of the original lot was recovered as cresyl violet and 40% as cresyl red. Separated materials were characterized by nuclear magnetic resonance and mass spectroscopy; UV-visible and Fourier-transform infrared spectra also were obtained for samples of pure cresyl violet and cresyl red. The colored constituents of the commercial dye lot were identified using thin layer chromatography and reverse phase high performance liquid chromatography. Both methodologies were suitable for routine testing; reverse phase high performance liquid chromatography is an appropriate tool for quality control and high resolution identification of these compounds.